A Dynamic Assessment of the François-Mitterrand Library - Vesque-Jeancard, Valerie (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
The François-Mitterrand Library, main site of the Bibliothèque nationale de France (BnF), was built in 1993 by architect Dominique Perrault. The library, which hosts 13 million documents, welcomes 3,500 visitors per day, either for consultation of documents in its majestic reading rooms or for conferences and exhibitions. The evolution of services provided to the library’s visitors (increase in electronic resources for instance), the broadening of the BnF’s users (from researchers to a broader public, including professionals and young people), the change in the building’s environment (public transportation, urban extension, etc.) along with the evolution of regulations (facilities for the disabled, etc.) or, more recently, increased consideration for sustainable development, led to a continuous adaptation of the building throughout the last 15 years. This dynamic assessment will continue to be a key factor for the library to successfully face future challenges.